Association, emulsifying, and solubilization properties of amphiphilic hyperbranched poly(acrylic acid) with short polystyrene stickers. Issue 1 (29th October 2013) - Li, Lianwei; Wang, Xu; He, Chen; He, Weidong
ABSTRACT Amphiphilic hyperbranched copolymer chains made of large hyperbranched poly(acrylic acid) cores grafted with short polystyrene stickers (HB‐PAAn‐g‐PSn + 1) with different n values (n = 1, 10, 47) were well prepared and confirmed by size exclusion chromatography, Fourier transform infrared spectroscopy and 1H nuclear magnetic resonance. The study on the interchain association behavior of these amphiphilic chains indicates that larger HB‐(PAA)n‐g‐(PS)n + 1 copolymer chains have a less tendency to undergo interchain association. Moreover, the simple vial‐inversion and rheological experiments show that the apparent critical gel concentration (Cg) decreases with n, but no sol–gel transition was observed for triblock PS‐PAA‐PS even when the concentration is up to 200 g L−1. Further transmission electron microscopy study of the latex particles prepared with HB‐(PAA)n‐g‐(PS)n + 1 as surfactant reveals that the latex particles are spherical and narrowly dispersed; while the measured latex particle number (Np) indicates the surfactant efficiency of HB‐(PAA)47‐g‐(PS)48 is poorer than that of triblock PS‐PAA‐PS (n = 1). Finally, pyrene solubilization measurement shows the solubilization efficiency of HB‐(PAA)n‐g‐(PS)n + 1 copolymers decreases with n, consistent with the previous observed interchain association result. The present study demonstrates that both the chain topology and the styrene weight fraction dominates the final solution properties of amphiphilic HB‐(PAA)n‐g‐(PS)n + 1 chains in aqueous solution. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 128–138